The conscious brain how attention engenders experience - Prinz, Jesse J. (New York ; Oxford : Oxford University Press, 2012)
Synthesizing decades of research, this book advances a theory of the psychological and neurophysiological correlates of conscious experience. Prinz argues that consciousness always arises at a particular stage of perceptual processing, the intermediate level, and that consciousness depends on attention.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Consciousness; Experience; Attention